2021
DOI: 10.3390/mi12060710
|View full text |Cite
|
Sign up to set email alerts
|

Medical Applications of Diode Lasers: Pulsed versus Continuous Wave (cw) Regime

Abstract: The paper deals with the medical application of diode-lasers. A short review of medical therapies is presented, taking into account the wavelength applied, continuous wave (cw) or pulsed regimes, and their therapeutic effects. Special attention was paid to the laryngological application of a pulsed diode laser with wavelength 810 nm, and dermatologic applications of a 975 nm laser working at cw and pulsed mode. The efficacy of the laser procedures and a comparison of the pulsed and cw regimes is presented and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…27 The diode laser has important advantages, such as good coagulation properties, absence of postoperative bleeding and pain, and good wound healing. 9 Consequently, it provides a better postoperative appearance, with less edema, bleeding, infection, and pain and thereby less need for postoperative analgesics. In our experience, in the trans-application of FDIP, approximately half of the patients felt a burning sensation, while 66% had edema and 4.2% had bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The diode laser has important advantages, such as good coagulation properties, absence of postoperative bleeding and pain, and good wound healing. 9 Consequently, it provides a better postoperative appearance, with less edema, bleeding, infection, and pain and thereby less need for postoperative analgesics. In our experience, in the trans-application of FDIP, approximately half of the patients felt a burning sensation, while 66% had edema and 4.2% had bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7 In FDIP, the diode laser is useful because it is highly absorbed by chromophores, such as hemoglobin, melanin, and collagen, and because it can cut and coagulate soft tissue, providing hemostasis and efficient tissue ablation. 8,9 Once the laser has penetrated the tissue, it generates heat with coagulation capacity at a depth of 7.0 to 10.0 mm, a process called photocoagulation. 10,11 In this process, energy is released through an optical fiber, maintained between 2.0 and 3.0 mm without contact with the target tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid Keywords anesthesia; energy; histological examination; cellular; cell distortions; epidermal 2 localized heating generates substantial thermal transients and shock waves, which can propagate into the blood vessels of the dermal tissue layers. Data showed that structural proteins such as collagens underwent denaturation at temperatures exceeding 60-70 o C [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…There are six papers published in this Special Issue focusing on pulsed laser machining. From metallic [1,2], inorganic [3] and polymeric [4,5] materials to biomass materials [6], from surface texture microstructures [1] and grain microstructures [2] to various types of functional contour structures [4,5], from the laser processing of metallic materials [1,2] and inorganic nonmetallic materials [3] to polymeric materials [4,5], from flexible electronics [4,5] and new energy batteries [1] to biomedicine [6], the articles in this Special Issue explore the specific applications of pulsed lasers in various fields.…”
mentioning
confidence: 99%
“…In the pulsed laser processing of biomass materials, Michalik et al [6] deals with the medical application of diode-lasers. A short review of medical therapies is presented, considering the wavelength applied, continuous wave (cw) or pulsed regimes, and their therapeutic effects.…”
mentioning
confidence: 99%